Measuring the Biases, Burdens, and Barriers Women Entrepreneurs Endure in Myanmar - Dall'Aglio, Chiara; Hayati, Fayavar; Lee, David (World Bank, Washington, DC, 2020)
Entrepreneurs in Myanmar face many challenges to starting and operating a business. As is the experience globally, women often experience these challenges to a greater extent and face additional sociocultural barriers, limiting their equal participation in the economy. To develop a better understanding of the dynamics holding back private sector development, especially for women, this paper uses data from the first-of-a-kind, firm-level data set available in Myanmar. The analysis explores the variance of experience female-owned micro, small, and medium-size enterprises face compared with their male-owned counterparts. The paper assesses the barriers imposed on entrepreneurs and their businesses and identifies firm-level characteristics leading to the use of good business practices. Further, the analysis investigates the adoption of gender and family-friendly policies, as an outcome and as a determinant of business success. The purpose of the study is to gain a better understanding of the barriers to gender-inclusive private sector development in Myanmar and provide tangible recommendations to private- and government-level actors. Overall, the analysis finds the major constraints for women entrepreneurs are access to finance and sociocultural factors, such as family responsibilities and household work.